2012
DOI: 10.1371/journal.pone.0044050
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Review Boards’ Use and Understanding of Certificates of Confidentiality

Abstract: Certificates of Confidentiality, issued by agencies of the U.S. government, are regarded as an important tool for meeting ethical and legal obligations to safeguard research participants’ privacy and confidentiality. By shielding against forced disclosure of identifying data, Certificates are intended to facilitate research on sensitive topics critical to the public’s health. Although Certificates are potentially applicable to an extensive array of research, their full legal effect is unclear, and little is kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In crafting our simplified language, we attempted to remain faithful to the substance of NIH’s version, which states: “With this Certificate, the researchers cannot be forced to disclose information that may identify you, even by a court subpoena.” Despite this strong assertion, it is unclear whether Certificates can provide such absolute protection in all circumstances (Beskow et al 2012; Beskow, Dame, and Costello 2008, 2009; Wolf et al 2012). Thus, developing consent descriptions of Certificates that are both simple and accurate is critically important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In crafting our simplified language, we attempted to remain faithful to the substance of NIH’s version, which states: “With this Certificate, the researchers cannot be forced to disclose information that may identify you, even by a court subpoena.” Despite this strong assertion, it is unclear whether Certificates can provide such absolute protection in all circumstances (Beskow et al 2012; Beskow, Dame, and Costello 2008, 2009; Wolf et al 2012). Thus, developing consent descriptions of Certificates that are both simple and accurate is critically important.…”
Section: Discussionmentioning
confidence: 99%
“…The research enterprise depends on public confidence that participants’ confidentiality will be vigorously protected (Beskow et al 2012). Authorized by federal law (Public Health Service Act §301(d), 42USC §241(d)), Certificates of Confidentiality are an important tool for meeting this ethical and legal obligation.…”
Section: Introductionmentioning
confidence: 99%
“…146 As a result, the certificate mechanism has been significantly under-utilized by biobanks (a 2003 study found that only 1 of 12 major biobanks in the U.S. had obtained a certificate, and only about quarter of IRBs would require or recommend it). 146,149 We have yet to see whether the NIH will endorse—and implement—the recommendation of the planners of the All of Us Research Program that all users of identifiable data be required to secure a certificate. 143 In the meantime, concern remains for all biobanks and genetic research settings, and significantly, for clinical testing laboratories, a domain not covered by a certificate.…”
Section: The Future Of Behavioral Genetic Evidence In Courtmentioning
confidence: 99%
“…Study investigators, research subjects, IRBs, and legal counsel differ in their knowledge level and familiarity with COCs (Coffey and Ross 2004; Catania et al 2007; Beskow 2012; Wolf et al 2012). In part, differences arise because only one court has spoken directly to the issue of the Certificate’s validity, upholding the COC, and promoting a widespread belief of absolute protection of confidentiality under COCs (Beskow, Dame, and Costello 2008).…”
Section: What Protection Does the Certificate Of Confidentiality Provmentioning
confidence: 99%